Role of Islamic Finance Development to Financial Inclusion: Empirical Study in Islamic Banking Countries - Priyonggo Suseno; Yeny Fitriyani (Jurnal Ekonomi & Keuangan Islam, 2018)
AbstractThe purpose of this paper is to determine the level of regional financial inclusion in OIC countries which operate Islamic Banking and the link between financial inclusion and Islamic finance development. This is the first study of that investigate the role if Islamic finance to financial inclusion which include Islamic financial development and societal variables as independent variables. Panel data regression has been used to estimate the relationship between Islamic finance development and financial inclusion. EGLS, Estimated Generalize Least Square, is being used to reduce the autocorrelation among residual due to cross-sectional effect. Using Sharma Financial Inclusion Index, this study finds that the average Financial Inclusion Index is 22.2 with the highest index is 62.6 and the lowest index is 2.1.  Based on panel data regression, this study finds that macro-economic factors, level of employment and GDP per capita, have the most significant influences on financial inclusion in Islamic banking countries. Other non-economic societal factors such as information technological advancement and corruption level do not significant influence on financial inclusion.Keywords --Panel regression, Financial Inclusion, Islamic Financial Development